Breast cancer in young patients. Peculiarities of prognosis and adjuvant hormone therapy (a literature review) - D. N. Kravchenko; A. A. Parokonnaya; M. I. Nechushkin; E. A. Nikitina; N. D. Hakurinova (Опухоли женской репродуктивной системы)
Breast cancer (BC) keeps being the most predominant malignant disease in women. In recent years, a trend towards “rejuvenescence” of the disease has been observed that affects its features. Despite modern methods of diagnosis and complex treatment used in young patients, survival in this age group are inferior that’s associated with biological and morphological peculiarities of BC in young age. Gradually are being collected data according to what age might be an independent factor exacerbating prognosis. For BC patients younger 40 years, various aspectsof hormone therapy remain ambiguous: prolonged tamoxifen use, aromatase inhibitors prescription, ovarian function suppression, a role of chemotherapy-induced amenorrhea on prognosis. The issue of appropriate, personalized adjuvant hormone therapy of BC is complex and heterogenous that requires a necessity to further conduct international randomized trials.